A fluorescent reporter and single-turnover kinetics reveal insight into BAM complex function - Whitney Nicole Bergman; Marcelo Carlos Sousa (Proceedings of the National Academy of Sciences, 2025)
The β-barrel assembly machine (BAM) is an essential protein complex that folds and inserts outer membrane β-barrel proteins (OMPs) into the bacterial outer membrane. The BAM complex contains the essential BamA OMP with five soluble polypeptide transport-associated (POTRA) domains, which scaffold the essential BamD lipoprotein and the nonessential lipoproteins BamB/C/E. The importance of each BAM component has been investigated primarily using cell-based phenotypic assays, and structural data have revealed insights into the role of the BamA β-barrel in OMP folding. However, in vitro quantitative analysis for the function of each BAM component has been challenging. We describe the development of a fluorescent reporter of OMP folding, bOmpA-A488, which we use to obtain single-turnover kinetic parameters for wild-type BAM complex in vitro. We observe a k fold of 0.78 ± 0.15 min −1 and approximate substrate affinity of 3.1 ± 1.1 µM consistent with estimates of in vivo requirements. Furthermore, we find that while BamA alone is inactive in Escherichia coli lipid liposomes, BamAB and BamAD subcomplexes have activities similar to that of the holoBAM complex. This suggests that OMP folding and insertion is catalyzed by BamA while the accessory lipoproteins maintain BamA in a catalytically competent conformation. We also find that, contrary to prevailing models, POTRA domain deletions that include POTRA3, which is essential in cells, do not drastically impact activity. This indicates that the first three POTRA domains do not play a major role in binding or folding OMPs under single-turnover conditions, suggesting a different role in cells.